Introduction to the Symposium - Celis López, Alfredo (2023)
Sexual and reproductive health, defined as the physical, mental, and social state related to sexuality and the reproductive capacity of individuals, involves various aspects and procedures, some of which are controversial and raise ethical dilemmas regarding what is considered morallycorrect. Bioethics is a discipline concerned with examining the ethicaldilemmas that arise in the field of health and biology. In the contextof sexual and reproductive health it plays a crucial role in addressingreproduction, fertility control, sexual health, and other related issues.